Spinel M0.5Zn0.5Fe2O4 (M = Ni, Co, and Cu) ferrites for energy storage applications: Dielectric, magnetic and electrochemical properties. Issue 19 (1st October 2022) - Khan, Shehzad; Ali, Basit; Salman, Muhammad; Muhammad, Raz; Khan, Majid; Hussain, Fayaz; Song, Kaixin; Wang, Dawei
Abstract: Spinel structured M0.5 Zn0.5 Fe2 O4 (M = Ni, Co, Cu) were synthesized through a solid state route. Phase analysis of the samples showed the formation of a single phase spinel structure. Fourier transform infrared spectroscopy also confirm the presence of tetrahedral and octahedral sites belonging to spinel structure. The microstructural analysis of the samples revealed a grain size ranging from 0.5 to 3.7 μm. The photoluminescence spectroscopy indicated the generation of oxygen vacancies and structural defects in the lattice of the samples. The obtained dielectric constant and loss values (at 1 MHz) varied between 11 and 35, and 0.006 to 1.2, respectively. The variation in dielectric properties was dependent on polarization species, crystallite size, defects and oxidation states. The samples showed a ferromagnetic behavior at room temperature. The electrochemical performance of Cu0.5 Zn0.5 Fe2 O4 showed the most favorable results such as the lowest overpotential of 490 mV, the highest specific capacitance of 462 F/g, and the lowest charge-transfer resistance of 876 Ω, suggesting its potential for energy storage applications.